2019
DOI: 10.15171/apb.2019.052
|View full text |Cite
|
Sign up to set email alerts
|

Dihydropyrimidine Dehydrogenase Levels in Colorectal Cancer Cells Treated with a Combination of Heat Shock Protein 90 Inhibitor and Oxaliplatin or Capecitabine

Abstract: Purpose: Dihydropyrimidine dehydrogenase (DPD) is the principal enzyme in the catabolism of fluoropyrimidine drugs including capecitabine. A recent report has suggested that oxaliplatin chemotherapy is associated with elevated DPD levels and chemoresistance pattern. As a newly developed chemotherapeutic agent, 17-allyloamino-17-demethoxy-geldanamycin (17-AAG) can be effective in combination therapy with oxaliplatin and capecitabine in colorectal cancer (CRC). DPD expression level can be a predictive factor in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 33 publications
2
9
0
1
Order By: Relevance
“…Combination of 17-AAG and oxaliplatin or capecitabine in colorectal cancer cell lines has been studied. 17-AAG in combination with paclitaxel on anaplastic thyroid carcinoma cells has also been reported [29][30][31]. In this study, we con rmed that necroptosis was one of the important reasons of Sorafenib attacking HCC.…”
Section: Introductionsupporting
confidence: 77%
“…Combination of 17-AAG and oxaliplatin or capecitabine in colorectal cancer cell lines has been studied. 17-AAG in combination with paclitaxel on anaplastic thyroid carcinoma cells has also been reported [29][30][31]. In this study, we con rmed that necroptosis was one of the important reasons of Sorafenib attacking HCC.…”
Section: Introductionsupporting
confidence: 77%
“…The combination of 17-AAG and oxaliplatin or capecitabine in colorectal cancer cell lines has been studied. 17-AAG in combination with paclitaxel on anaplastic thyroid carcinoma cells has also been reported [ 28 , 29 , 30 ]. In this study, we confirmed that necroptosis was one of the important reasons why Sorafenib attacks HCC.…”
Section: Introductionmentioning
confidence: 99%
“…Colorectal cancer (CRC) is the third-largest cancer world width 1,2 and is related to a high rate of mortality. [1][2][3][4][5] Recently, clinical studies have been interested in detecting novel integrating targeted treatments and combination chemotherapy regimens. 2 Combination chemotherapy comes into importance in CRC treatment but drug resistance is inevitable.…”
Section: Introductionmentioning
confidence: 99%
“…3 In this regard, evaluating new drug combinations can improve the treatment outcomes. 3,5 Numerous efforts have been conducted for increase understanding of the CRC heterogeneity and propose the most effective-tailored treatment to any affected patient. 6 Since, oncogene mutations and the existence of multi-drug resistance, and the intolerable side effects limit the efficiency of treatment.…”
Section: Introductionmentioning
confidence: 99%